2019
DOI: 10.1042/bsr20190280
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA PFAR contributes to fibrogenesis in lung fibroblasts through competitively binding to miR-15a

Abstract: Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive, debilitating disease with unknown etiopathogenesis. Previous reports have reported that long non-coding RNAs (lncRNAs) were involved in various pathophysiological processes. However, the role of lncRNAs in IPF has not been fully described. We aimed to explore the relationship between miR-15a and lncRNA PFAR and its function in pulmonary fibrosis. Biological information analysis and luciferase were used to identify targeted binding of lncRNA PFAR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Numerous studies have reported the emerging role of lncRNAs in the pathogenesis of pulmonary fibrosis ( 19 21 ). A previous study found that NEAT1 was increased in human fibrotic liver samples and murine fibrotic livers ( 12 ), while Huang et al ( 13 ) reported that NEAT1 accelerated fibrosis in diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported the emerging role of lncRNAs in the pathogenesis of pulmonary fibrosis ( 19 21 ). A previous study found that NEAT1 was increased in human fibrotic liver samples and murine fibrotic livers ( 12 ), while Huang et al ( 13 ) reported that NEAT1 accelerated fibrosis in diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has confirmed that long noncoding RNAs (lncRNAs) are involved in many pathophysiological processes of PF, including cell proliferation, migration, epithelial-mesenchymal transition (EMT), and immunoregulation [7,8]. For example, Song et al found that the abnormal expression of lncRNA and protein-coding gene was associated with the progression of PF through as competing endogenous RNA (ceRNA) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicated that lncRNAs acted as a key mediator in various diseases, such as myocardial infarction, pulmonary fibrosis, breast cancer. [21][22][23] Interestingly, lncRNAs were involved in glioma progression. LncRNA PAXIP1-AS1 enhanced migration, invasion, and angiogenesis of human umbilical vein endothelial cells in glioma by recruiting the transcription factor ETS1 to upregulate the expression of KIF14.…”
Section: Discussionmentioning
confidence: 99%